Assessment of Potential Non-Tax Revenue in Malaysian Local Authorities (Journal of Business Management and Accounting, 2019)
Non-tax revenue trends and their potential have received less attention than property tax, which is the primary source for most Malaysian local authorities (LAs). This paper highlights the examination conducted on potentials and strategies adopted by each LA investigated to maximize return from non-tax revenue. In doing this, qualitative approach using secondary data acquired from financial reports and primary data from in-depth interviews was employed. Ten LAs were selected through purposive sampling. The trend of revenue collection among the selected LAs and the strategies to improve non-tax revenue collection through thematic analysis are highlighted. The analysis of the trend of local authorities’ revenue reveals that non-tax revenue remains the second most important after the tax revenue. However, Pulau Pinang City Council (MBPP) is the only LA that records an average of non-tax revenue exceeding 50 per cent of its total internal revenue. This study has also found that the divergence among the local authorities’ non-tax revenue collection is due to the revenue improvement strategies adopted by each local authority. Therefore, eight recommendations are made to improve non-tax revenue. Though this study is limited to 10 LAs as sample, the successful optimizing strategies highlighted from the study can represent an efficient model for other LAs, in improving their non-tax collection.